COMPARATIVE EVALUATION OF SERIES–PARALLEL HYBRID ARCHITECTURES FOR GASOLINE COMPRESSION IGNITION HEAVY-DUTY VEHICLES - Hery Tri Waloyo; Agus Mujianto (Trends in Mechanical Engineering Research, 2025)
The wede168 growing demand for sustainable propulsion in heavy-duty transport has intensified research on Gasoline Compression Ignition (GCI) engines integrated with hybrid powertrains. This review presents a comprehensive comparative evaluation of series–parallel hybrid architectures for GCI-powered heavy-duty vehicles, emphasizing energy efficiency, combustion stability, and emission performance. This study systematically analyzed publications from the SAE, IEEE, Elsevier, and Springer databases, published between 2015 and 2025, through a rigorous peer-reviewed selection framework. The results show that series–parallel configurations provide better power distribution between the GCI engine and the electric motor, achieving 8–15% higher fuel-to-wheel efficiency than conventional diesel hybrids. Thermal–energy coupling models improve heat management and combustion consistency, reducing NOx and particulate emissions by up to 45%. Additionally, the use of deep reinforcement learning (DRL) and model predictive control (MPC) enhances adaptive energy management under varying load conditions. However, challenges remain in maintaining combustion stability during transient operations and optimizing hybrid mode transitions. Overall, this review identifies the series–parallel GCI hybrid architecture as a promising intermediate technology bridging conventional diesel systems and future zero-emission solutions, particularly for long-haul and urban heavy-duty applications.